(untitled) (Indian Forester, 1950)
The progressive disintegration of the cellulose causes a gradual decrease in mechanical strength which in turn may result in failure by shearing. Such mechanical failures were first noticed in samples 260 years old (spruce and pine). Although deterioration of the cell walls is first observed in late wood the loss of strength on the other hand shows up earlier in early wood. Older samples showed a similarity with lignite and petrified wood samples and had a grainless structure and from these observations it is concluded that the changes in the cell walls of the wood fibre are identical with those which take place in wood during conversion to coal. As a further proof that the deterioration of wood in the soil under anaerobic conditions is not caused by fungi, the absence of hyphae and bore holes excepting in one case is cited.